Statistics and medical decision making. - Gouveia-Oliveira, A (1996)
Statistics is the science that studies variability in all its forms and, in essence, is an instrument that allows us to analyze variable phenomena and detect small, but nevertheless important, differences. The instrumental character of this science made Statistics a fundamental tool for the study of biological and clinical phenomena, but the purpose of this discussion is to focus on the fact that Statistics, either directly or indirectly, is presently the basis of virtually all medical decision-making processes and, consequently, has had a major influence on clinical practice itself. Disease prevalence, the consideration of risk factors, for instance, which is information of great importance in the process of diagnosis, is obtained through studies that are based in statistical methodologies. It is, however, in the decision-intensive processes of selecting diagnostic examinations, choosing the best therapy and evaluating the prognostic implications, that Statistics have had a more direct impact on clinical practice. In modern Medicine, Statistics may no longer be seen as a set of techniques that are applied in scientific research. Rather, Statistics should be understood as the appropriate language for describing and discussing observed phenomena.